Assessing the accuracy and performance of implicit solvent models for drug molecules: conformational ensemble approaches - Kolář, Michal; Fanfrlík, Jindřich; Lepšík, Martin; Forti, Flavio; Luque, F Javier; Hobza, Pavel (The journal of physical chemistry. B, 2013)
The accuracy and performance of implicit solvent methods for solvation free energy calculations were assessed on a set of 20 neutral drug molecules. Molecular dynamics (MD) provided ensembles of conformations in water and water-saturated octanol. The solvation free energies were calculated by popular implicit solvent models based on quantum mechanical (QM) electronic densities (COSMO-RS, MST, SMD) as well as on molecular mechanical (MM) point-charge models (GB, PB). The performance of the implicit models was tested by a comparison with experimental water-octanol transfer free energies (ΔG(ow)) by using single- and multiconformation approaches. MD simulations revealed difficulties in a priori estimation of the flexibility features of the solutes from simple structural descriptors, such as the number of rotatable bonds. An increasing accuracy of the calculated ΔG(ow) was observed in the following order: GB1 ~ PB < GB7 ≪ MST < SMD ~ COSMO-RS with a clear distinction identified between MM- and QM-based models, although for the set excluding three largest molecules, the differences among COSMO-RS, MST, and SMD were negligible. It was shown that the single-conformation approach applied to crystal geometries provides a rather accurate estimate of ΔG(ow) for rigid molecules yet fails completely for the flexible ones. The multiconformation approaches improved the performance, but only when the deformation contribution was ignored. It was revealed that for large-scale calculations on small molecules a recent GB model, GB7, provided a reasonable accuracy/speed ratio. In conclusion, the study contributes to the understanding of solvation free energy calculations for physical and medicinal chemistry applications.
Keywords: Electrons; rotace; Quantum Theory; voda; Water; Molecular Dynamics Simulation; léčivé přípravky; Pharmaceutical Preparations; kvantová teorie; Molecular Conformation; Solvents; Octanols; rozpouštědla; simulace molekulární dynamiky; oktanoly; elektrony; termodynamika; molekulární konformace; Thermodynamics; Rotation